Legal Certainty Regarding Detention by Investigators Based on Law Number 20 of 2025 Concerning the Criminal Procedure Code - Hendro Gunawan; Mhd Azhali Siregar; Henry Aspan (CV. Era Digital Nusantara, 2026)
Detention is a form of coercive measure in the criminal justice process that limits a person's right to personal liberty, so its implementation must be based on the principles of legal certainty, limitation of authority, and protection of human rights. The formation of Law Number 20 of 2025 concerning the Criminal Procedure Code is part of the reform of the criminal justice system in Indonesia that aims to strengthen the protection of suspects' rights and create a more objective, proportional, and accountable detention mechanism. However, the application of subjective conditions for detention still has the potential to give rise to multiple interpretations and opens up wide discretion for investigators. This study aims to analyze the legal certainty of detention by investigators based on Law Number 20 of 2025, specifically regarding the regulation of detention conditions and limitations on the authority of coercive measures, as well as examine the concept of subjective conditions for detention from the perspective of due process of law and human rights protection. This study uses a normative legal research method with a statutory, conceptual, and case approach, which is analyzed qualitatively based on primary, secondary, and tertiary legal materials. The research results show that Law Number 20 of 2025 brings significant changes through the formulation of more objective and measurable detention indicators. This reformulation strengthens the principle of legal certainty and limits the authority of law enforcement officers in the use of coercive measures. Furthermore, this new regulation aligns with the principles of due process of law and human rights protection, as detention must be based on objectively verifiable facts and circumstances. However, its effective implementation still requires technical guidelines, effective oversight, and increased professionalism of law enforcement officers to prevent abuse of authority in criminal justice practices.